Automated Identification and Shape Analysis of Chorus Elements in the Van Allen Radiation Belts. Issue 12 (28th December 2017) - Sen Gupta, Ananya; Kletzing, Craig; Howk, Robin; Kurth, William; Matheny, Morgan
Abstract: An important goal of the Van Allen Probes mission is to understand wave‐particle interaction by chorus emissions in terrestrial Van Allen radiation belts. To test models, statistical characterization of chorus properties, such as amplitude variation and sweep rates, is an important scientific goal. The Electric and Magnetic Field Instrument Suite and Integrated Science (EMFISIS) instrumentation suite provides measurements of wave electric and magnetic fields as well as DC magnetic fields for the Van Allen Probes mission. However, manual inspection across terabytes of EMFISIS data is not feasible and as such introduces human confirmation bias. We present signal processing techniques for automated identification, shape analysis, and sweep rate characterization of high‐amplitude whistler‐mode chorus elements in the Van Allen radiation belts. Specifically, we develop signal processing techniques based on the radon transform that disambiguate chorus elements with a dominant sweep rate against hiss‐like chorus. We present representative results validating our techniques and also provide statistical characterization of detected chorus elements across a case study of a 6 s epoch. Plain Language Summary: An important goal of the Van Allen Probes mission is to understand wave‐particle interaction by chorus emissions in Earth's Van Allen radiation belts. To test models, statistical characterization of chorus properties, such as amplitude variation and sweep rates, is an important scientific goal. The EMFISIS instrumentation suite provides measurements of wave electric and magnetic fields as well as DC magnetic fields for the Van Allen Probes mission. However, manual inspection across terabytes of EMFISIS data is not feasible and as such introduces human confirmation bias. We present signal processing techniques for automated identification, shape analysis, and sweep rate characterization of high‐energy whistler‐mode chorus elements in the Van Allen radiation belts. Specifically, we develop computational techniques that disambiguate chorus elements against hiss‐like chorus. We present representative results validating our techniques and also provide statistical characterization of detected chorus elements across a case study of a 6 s epoch. Key Points: Chorus elements exhibit morphological characteristics that are difficult to detect, classify, and document manually across terabytes of data We introduce signal processing and shape analysis techniques that enable automated detection and characterization of chorus elements Representative results over EMFISIS data demonstrate that chorus elements and their dominant sweep rates can be identified autonomously